PENGEMBANGAN KOMPETENSI GURU KELAS DALAM PELAKSANAAN PEMBELAJARAN BERNUANSA BIMBINGAN DI SEKOLAH LUAR BIASA MELALUI COMPETENCY BASED TRAINING - Nani Triani, - (2020)
The competence of classroom teachers in implementing of learning in special schools needs to be continuously developed and one of which is through Competency Based Training. This study aims to produce a Competency-Based Training program formulation to develop the competence of the classroom teachers in implementing guidance-nuanced learning in special schools. This research used a quantitative approach, with a quasi-experimental method and a one-group pretest-posttest design. The instrument used was a test involving 37 participants and t-test to analyze the obtained data. The results showed that: the competency profile of classroom teachers at implementing of learning in special schools in the cluster 38 before having attended the training was in the sufficient category; Competency-Based Training program formulation can be used as a classroom teacher competency development program at implementing guidance-nuanced learning in special schools; and the average score of the classroom teachers' competency in special schools is 65.73, and it belongs to the sufficient category with a standard deviation of 5,853 before having participated in the training and the average competency is 76.54, is in the good category after having taken the training with a standard deviation of 6,611 and statistical value of t = 17.31, with db = 36 and p-value = 0.000 <0.05. Therefore, it can be concluded that the Competency-Based Training program is effective in developing the competence of classroom teachers in special schools in implementing guidance-nuanced learning in cluster 38, Bandung Regency